2020
DOI: 10.1186/s12871-020-00974-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of cases of intraoperative awareness in a large multi-hospital health system reported in the early postoperative period

Abstract: Background: Awareness with recall under general anesthesia remains a rare but important issue that warrants further study. Methods: We present a series of seven cases of awareness that were identified from provider-reported adverse event data from the electronic anesthesia records of 647,000 general anesthetics. Results: The low number of identified cases suggests an under-reporting bias. Themes that emerge from this small series can serve as important reminders to anesthesia providers to ensure delivery of an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The excess adipose tissue, higher circulating blood volume, and elevation in cardiac output results in changes to the volume of distribution, protein binding and drug elimination of most drugs, making safe and effective dosing of medications challenging [19]. For example, some studies have shown evidence of an increased risk for intraoperative awareness in obese patients [20]. Yet at the same time, other studies have shown that obese patients are prone to anesthetic overdosage leading to a higher degree of cardiovascular depression as compared to nonobese patients [21].…”
Section: Anesthetic Considerations In the Bariatric Patientmentioning
confidence: 99%
“…The excess adipose tissue, higher circulating blood volume, and elevation in cardiac output results in changes to the volume of distribution, protein binding and drug elimination of most drugs, making safe and effective dosing of medications challenging [19]. For example, some studies have shown evidence of an increased risk for intraoperative awareness in obese patients [20]. Yet at the same time, other studies have shown that obese patients are prone to anesthetic overdosage leading to a higher degree of cardiovascular depression as compared to nonobese patients [21].…”
Section: Anesthetic Considerations In the Bariatric Patientmentioning
confidence: 99%
“…[ 1 3 ] Low anaesthesia increases the risk of intraoperative awareness and adverse cardiovascular events, cerebrovascular events, and stress responses. [ 4 , 5 ] Therefore, it is crucial to identify a means to guide individually anaesthetized patients to improve postoperative recovery and avoid anaesthesia-related complications.…”
Section: Introductionmentioning
confidence: 99%